Merchandise trade of the unrecognized entities in West Asia. The gravity model of trade, including Abkhazia and South Ossetia - Suska Magdalena (International Journal of Management and Economics, 2023)
The study aims at presenting the specificity of the economy and merchandise trade of unrecognized entities in the Caucasus region, with a particular focus on Abkhazia and South Ossetia. The study also analyses the potential changes in merchandise trade structure and volume. The empirical analysis covers the period between 2015 and 2020. The conducted study has revealed that over the last years, Abkhazia and South Ossetia have improved their economic condition, increasing industrial production, developing services, and maintaining trade exchange with other states. However, as the outcomes of the gravity model of trade indicate, both unrecognized entities do not fully utilize its trade potential, especially with Georgia, Russia, and Turkey. Hence legitimizing trade between Abkhazia and South Ossetia may bring economic benefits not only for both entities but also for other countries, especially their immediate neighbors.